Cellulose‐Based Soft Actuators. Issue 6 (18th April 2022) - Chen, Wenbo; Sun, Bianjing; Biehl, Philip; Zhang, Kai
Abstract: Compared to other commonly used materials in the field of soft actuators, cellulose offers many advantages such as low cost, sustainability, versatile applications, and abundancy. Due to the enormous and growing demand in the functional flexible electronics industry, cellulose‐based soft actuators are receiving a lot of attention and are undergoing an exciting development. In this focused review, the milestones and recent achievements of cellulose‐based actuators are presented. The actuation energy of the actuators is mainly generated through external stimuli like electricity, temperature, magnetic fields, light, or moisture. Different systems which use these stimuli and corresponding fabrication techniques for these materials, such as self‐assembly and layer by layer deposition are discussed. Further, the currently applied strategies to achieve programmable actions in soft actuators will be reviewed, which allow control over responding deformation. Finally,  the pending challenges and some potential solutions in the upcoming development of cellulose‐based actuators are summarized. Abstract : This review includes the design, materials, fabrication, and applications of cellulose‐based actuators. The cellulose resources including polymeric cellulose chains, nanocellulose and macroscopic cellulose fiber as well as their derivatives with the integration of other compounds for the soft actuators are summarized. The prospect and limitations of cellulose‐based actuators are also discussed in this review.